Alteration of the Inflammatory and Anti-Inflammatory Cytokine Profiles of Peripheral Blood Mononuclear Cell in Crohn's Disease Patients after Following up - Fatemeh Ghasemi; Vahid Basirat; Maryam Izad; Mohammad Javad Tavassolifar; Mehdi Yaseri; Nasser Ebrahimi Daryani; Masoud Alebouyeh; Mohammad Reza Pourmand (Tehran University of Medical Sciences, 2022)
Background: Crohn's disease (CD) has a chronic course, which its recurrence varies widely among different patients. In this study we prospectively analyzed blood samples of 19 CD patients. Alteration in transcription of inflammatory and anti-inflammatory cytokines was analyzed compared with household members after three month follow up. Methods: CD patients were diagnosed based on clinical symptoms, endoscopic and histopathologic characteristics. Nineteen CD patients and their households were evaluated from Jun 2019 to Feb 2021 at Tehran university hospitals. CD activity score, biological, clinical and demographic data of the patients were recorded at two time point intervals. Bacteriological tests were done using aerobic and anaerobic blood cultures. To investigate transcriptional alterations, peripheral blood mononuclear cells (PBMCs) were isolated using Ficol centrifugation method and relative quantitative real-time PCR was done to determine the expression level of IFN-γ, TNF-α, IL10, and FOXP3 cytokines. Results: Our results showed a correlation between fecal calprotectin level (709.8 ± 554.6), C-reactive protein concentration (18.1 ± 15.9), and erythrocyte sedimentation rate (30.4 ± 17.9) with disease activity (Flare/remission). IL10 and Foxp3 anti-inflammatory gene's expression were significantly (P = 0.003 for IL10 and P = 0.008 Foxp3) higher during the flare and remission in patients with active disease respectively. Bacteriological examination showed infection with Streptococcus spp. and Clostridium spp. in two CD patients during flares, which was correlated with upregulation and down-regulation of IL10, TNF-α, IFN-γ and FOXP3 proteins, respectively. Conclusion: Occurrence of bacteremia, and higher amount of CAP, CRP and ESR are correlated with higher level of transcription for inflammatory cytokines, which could effectively reflect the disease activity. Raise in FoxP3 transcription proposed change in Treg sub-population in PBMC or its activity during the CD remission phase.